Plasmid Display for Stabilization of Enzymes Inside the Cell to Improve Whole-Cell Biotransformation Efficiency - Park, Yunjeong; Shin, Jonghyeok; Yang, Jinkyeong; Kim, Hooyeon; Jung, Younghun; Oh, Hyunseok; Kim, Yongjoon; Hwang, Jaehyeon; Park, Myeongseo; Ban, Choongjin; Jeong, Ki Jun; Kim, Sun-Ki; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Recombinant whole-cell biocatalysts are widely used for biotransformation of valuable products. However, some key enzymes involved in biotransformation processes are unstable and cannot be easily expressed in the functional form. In this study, we describe a versatile platform for enzyme stabilization inside the cell: Intracellularly Immobilized Enzyme System (IIES). A 1,2-fucosyltransferase from Pedobactor saltans (PsFL) and a 1,3-fucosyltransferase from Helicobacter pylori (HpFL), chosen as model proteins, were fused with Oct-1 DNA-binding domain, which mediated the formation of a plasmid–protein complex. Oct-1 fusion enabled both soluble and stable expression of recombinant proteins in the cytoplasm because the fusion proteins were stabilized on the plasmid like immobilized enzymes bound to solid surface. As a result, Oct-1-fusion proteins exhibited significantly greater product titer and yield than non-fusion proteins. Use of fusion proteins PsFL-Oct-1 with C-terminal Oct-1 and Oct-1-PsFL with N-terminal Oct-1 resulted in ~3- and ~2-fold higher 2'-fucosyllactose titers, respectively, than with the use of PsFL alone. When Oct-1 was fused to HpFL, which requires dimerization through heptad repeats, almost two times more 3-fucosyllactose was produced. IIES using Oct-1 fusion protein will contribute to the development of whole-cell biocatalysts in which recombinant enzymes are unstable under reaction conditions.